2012
DOI: 10.7554/elife.00205
|View full text |Cite
|
Sign up to set email alerts
|

KDM2B links the Polycomb Repressive Complex 1 (PRC1) to recognition of CpG islands

Abstract: CpG islands (CGIs) are associated with most mammalian gene promoters. A subset of CGIs act as polycomb response elements (PREs) and are recognized by the polycomb silencing systems to regulate expression of genes involved in early development. How CGIs function mechanistically as nucleation sites for polycomb repressive complexes remains unknown. Here we discover that KDM2B (FBXL10) specifically recognizes non-methylated DNA in CGIs and recruits the polycomb repressive complex 1 (PRC1). This contributes to his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
510
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(545 citation statements)
references
References 85 publications
34
510
0
1
Order By: Relevance
“…13 The high heterogeneity of PRC1 complexes is thought to allow a combinatorial assembly of multiple subunits to integrate additional biochemical activities including readers for other histone modifications-such as HP1s or the Malignant Brain Tumor (MBT) family members 26 -as well as histone modifiers-such as HDACs. 11 In the mouse embryo, PcG proteins support 'facultative' heterochromatin establishment in the male pronucleus 3,25,28 , and a mutation in K27 within H3.3, the main histone variant incorporated in the male pronucleus, results in developmental arrest and heterochromatin defects. 27 In addition, the combined deletion of both RING1 subunits, RING1A and RING1B, results in developmental arrest before the 2-cell stage due to defective regulation of the transcriptional program of the oocyte.…”
Section: Introductionmentioning
confidence: 99%
“…13 The high heterogeneity of PRC1 complexes is thought to allow a combinatorial assembly of multiple subunits to integrate additional biochemical activities including readers for other histone modifications-such as HP1s or the Malignant Brain Tumor (MBT) family members 26 -as well as histone modifiers-such as HDACs. 11 In the mouse embryo, PcG proteins support 'facultative' heterochromatin establishment in the male pronucleus 3,25,28 , and a mutation in K27 within H3.3, the main histone variant incorporated in the male pronucleus, results in developmental arrest and heterochromatin defects. 27 In addition, the combined deletion of both RING1 subunits, RING1A and RING1B, results in developmental arrest before the 2-cell stage due to defective regulation of the transcriptional program of the oocyte.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Fbxl10 was also recently reported to mediate the monoubiquitination of the histone H2A at lysine 119 as a component of noncanonical polycomb-repressive complex 1 in embryonic stem (ES) cells. 9,10 Several lines of evidence have so far suggested that Fbxl10 is a tumor accelerator. Overexpression of Fbxl10 in fibroblasts inhibited cellular senescence by repressing p16ink4a-p19Arf and p15ink4b loci in mouse as well as Rb and p53 loci in humans, resulting in cellular immortalization.…”
mentioning
confidence: 99%
“…Biochemical analyses identified BCOR as a complex comprising ring finger protein 2 (RFN2)/ring finger protein 1B (RING1B), polycomb group ring finger 1 (PCGF1)/nervous system polycomb 1 (NSPC1), lysine-specific demethylase 2B (KDM2B)/ F-box and leucine-rich repeat protein 10 (FBXL10), BCOR-like 1 (BCORL1), Ring 1 and YY1 binding protein (RYBP), YY1-associated factor 2 (YAF2), and S phase kinaseassociated protein 1 (SKP1; refs. [2][3][4]. The BCOR complex components are similar to the polycomb repressive complex 1 (PRC1) components ( Fig.…”
Section: The Bcl6 Corepressor Complex As a Repressive Transcriptionamentioning
confidence: 91%
“…KDM2B recruits the BCOR complex to nonmethylated CpG islands (CGI) through the ZF-CxxC DNA-binding domain of KDM2B (Fig. 1), not through H3K27me3-dependent targeting mechanisms (4,7). In addition, ChIP-seq analysis of embryonic stem (ES) cells revealed that KDM2B was enriched near transcription start sites, including Hox gene loci (7).…”
Section: The Bcor Complex Is a Distinct Subtype Of Prc1mentioning
confidence: 99%